DIGITAL THERAPEUTICS AND MENTAL HEALTH; THE ROLE OF DIGITAL THERAPEUTICS IN CONTEMPORARY CARE - Meliyeva Sh; Rakhimov B. B. (Web of Journals Publishing, 2025)
In this article is discussed the expanding field of digital therapeutics (DTx) and its intersection with mental health care. It outlines how the integration of digital tools into healthcare systems represents a transformative shift in the prevention, management, and treatment of mental health disorders.
Keywords: Digital therapetics, mental health, disease, application, healthcare, evidence, disorders.